The association of RAR‐related orphan receptor A (RORA) gene polymorphisms with the risk of asthma. (28th December 2017) - Cai, Xulong; Lin, Mali; Cao, Shan; Liu, Yunguang; Lin, Na
Abstract: Asthma is a common, heterogeneous chronic respiratory disease characterized by chronic inflammation of the airway, airway hyperreactivity, and airway remodeling. The RAR‐related orphan receptor A ( RORA ) gene has been identified for the pathogenesis of asthma. The purpose of this research was to investigate the relationship between RORA gene polymorphisms and asthma susceptibility in the Chinese Zhuang population. This was a case–control study including 231 children with asthma and 343 healthy controls. The RORA gene polymorphisms were measured by the polymerase chain reaction–ligase detection reaction genotyping assays and confirmed by sequencing. The distribution of the genotype frequencies of the RORA rs11071559 C>T was significantly different in the group of cases and the healthy children ( P  < 0.05). By haplotype analyses, the haplotype TT (rs7164773/rs11071559) was statistically significant between asthmatics and nonasthmatics, but the association was not significant after correction for multiple comparisons. Our results provided evidence that the RORA rs11071559C>T polymorphism was associated with an elevated susceptibility to pediatric asthma in the Chinese Zhuang population.